Determinants of Citizen Awareness and Participation in Smart City Initiatives: Insights from Sri Lanka - Wickramasinghe, Mihiri (School of Industrial and System Engineering, Telkom University, 2025)
Initiatives for Smart Cities present an acceptable solution to the issues of urban administration as urbanization gains increasing speed. However, the success of smart city initiatives depends on citizen awareness and participation. This study aims to identify the key determinants of awareness and participation in Smart City initiatives among Sri Lankan citizens. A cross-sectional survey was conducted using a structured self-administered questionnaire distributed via social media, with 200 respondents from all nine provinces. Convenience sampling was employed to ensure broad participation. Findings indicate that access to ICT, digital literacy, and community engagement significantly enhance awareness, which in turn fosters participation. Notably, perceived benefits do not significantly impact awareness but directly negatively affect participation, suggesting that concerns over potential risks may deter engagement despite increased awareness. These findings suggest that while community engagement, digital literacy, and access are useful for raising awareness, resolving citizens’ concerns about the potential risks of smart city initiatives is essential to increasing participation. Policymakers must prioritize trust-building measures and community engagement to overcome barriers to Smart City adoption. Future research could examine these relationships longitudinally and explore additional factors such as trust in government and technology acceptance.